Transformation of dimetallacyclopentanes into beta-substituted enamine-, alkylidene-, and alpha,beta-unsaturated acyl-bridged diiron complexes - Doherty, S; Hogarth, G; Elsegood, M; Clegg, W; Rees, N; Waugh, M (1998)
Nucleophilic addition of primary amines RNH2 to Cβ of the diiron allenyl complex [Fe2-(CO)6(μ-PPh2){μ-η 1:η2(H)C=C=CH2}] (1) affords the zwitterionic dimetallacyclopentane derivatives [Fe2(CO)6(μ-PPh2){μ-η 1:η1-H2C-C(NHR)-CH2}] (R = Pri (2a), CH2Ph (2b), CeH11 (2c), Prn (2d)). In refluxing toluene, 2a-d rearrange to give the nitrogen-coordinated organodiiron α,β-unsaturated amines [Fe2(CO)5(μ-PPh2){μ-η 1(C):η2(C):η1(N)-(H)C=CCH 3-(NHR)}] (R = Pri (3a), CH2Ph (3b), C6H11 (3c), Prn (3d)) via loss of carbon monoxide a 1,3-hydrogen migration, and coordination of the β-amino group. The bridging hydrocarbon in 3a-d adopts a highly unusual exo conformation with respect to the phosphide ligand. Compounds 3a-d are the first diiron β-substituted enamine complexes to be isolated and structurally characterized. Such compounds have previously been proposed as short-lived intermediates which readily isomerize to their alkylidene-bridged counterparts. Complexes 3a and 3c react with trimethyl phosphite to afford the stable alkylidene valence isomers [Fe2(CO)5{P(OMe)3}(μ-PPh 2){μ-CHC(CH3)(NHR)}] (R = Pri (4a), C6H11 (4c)). In contrast, in refluxing toluene, 2a-b react with trimethyl phosphite to give the α,β-unsaturated bridging acyl complexes [Fe2(CO)5{P(OMe)3}(μ-PPh 2){μ-O=C-CH=CMe(NHR)}] (R = Pri (5a), CH2Ph (5b)), which probably result from the formal insertion of carbon monoxide into an alkylidene intermediate. Single-crystal X-ray analyses of 5a and 5b showed the position of substitution to be the iron atom σ-bonded to the acyl oxygen, trans to the phosphido bridge in 5a and trans to the iron-iron bond in 5b. Variable-temperature 31P{1H} and 31P-31P 2D exchange NMR studies have been used to examine an exchange process that equilibrates two isomers of 4a and 5b, which differ in the position of the trimethyl phosphite. At low temperature, 4a exists as a 4:1 mixture of these two substitutional isomers, while at room temperature they are in fast exchange, on the NMR time scale. The free energy of activation associated with this exchange (ΔG‡273 = 9.5 kcal mol-1, 4a; ΔG‡273 = 10.4 kcal mol-1, 5b) is fully consistent with a restricted trigonal twist at the phosphite-substituted iron center. This exchange process also appears to be common to the alkylidene derivative 5b, which has similar 31P{1H} line broadening characteristics and free energy of activation. Full structural details of compounds 2a, 3a, 4c, 5a, and 5b are reported.